Sorption of Rare-earth Elements and Ac on DN resin with HCl, HClO4, CH3COOH, CCl3COOH. Issue 5 (29th July 2018) - Marinov, Genko Marinov; Marinova, Atanaska Pavlova; Milanova, Maria Milinova; Happel, Steffen; Karaivanov, Dimitar Veselinov; Filosofov, Dmitry Vladimirovich
ABSTRACT: The distribution of some rare-earth elements (REE) on DN resin (TODGA loaded resin by Triskem international) was determined from different concentrations of two inorganic (HCl, HClO4 ) and two organic acids (CH3 COOH, CCl3 COOH). The separation of Ac from REE is researched, as well as some separation possibilities of the elements within the REE. The determined distribution coefficients allows the prediction of the elution profiles of the researched elements. Using the obtained results in this work further applications can be considered.